2012
DOI: 10.1108/13527601211195655
|View full text |Cite
|
Sign up to set email alerts
|

EI training and sales performance during a corporate merger

Abstract: Purpose: To examine statistically the efficacy of an emotional intelligence training program on sales performance and emotional intelligence in a group of salespeople. Design/methodology/approach: An experimental, repeated measures/betweengroups design was used (training group (N = 29) and a control group (N = 21)). The dependent variables were sales performance, self-report EI and rater-report EI. The data were analysed based on a series of split-plot ANOVAS. Findings: Rater-reported EI correlated with sales … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 30 publications
3
10
0
1
Order By: Relevance
“…Recent research suggests that ESC are more powerful predictors of performance than global personality measures . Such findings are supportive of the criterion validity of ESC reported by others (Boyatzis, 1982(Boyatzis, , 2006Spencer and Spencer, 1993;McClelland, 1998;Goleman, 1998;Dulewicz et al, 2003;Boyatzis and Ratti, 2009;Ryan et al, 2009) and is in contrast to other commentary in the field of emotional intelligence which frames emotional and social intelligence as equivalent to existent personality constructs (McCrae, 2000;Newsome et al, 2000;Bastian et al, 2005).…”
supporting
confidence: 84%
“…Recent research suggests that ESC are more powerful predictors of performance than global personality measures . Such findings are supportive of the criterion validity of ESC reported by others (Boyatzis, 1982(Boyatzis, , 2006Spencer and Spencer, 1993;McClelland, 1998;Goleman, 1998;Dulewicz et al, 2003;Boyatzis and Ratti, 2009;Ryan et al, 2009) and is in contrast to other commentary in the field of emotional intelligence which frames emotional and social intelligence as equivalent to existent personality constructs (McCrae, 2000;Newsome et al, 2000;Bastian et al, 2005).…”
supporting
confidence: 84%
“…Interestingly, both self‐report and observer‐report scores of typical EI performance support the same model of EI (Gignac, in press), and self‐observer scores converge to a moderate degree (Gignac, 2010). Furthermore, both self‐report and observer‐report scores appear to be associated with predictive validity (e.g., Gignac, 2008; Gignac, Harmer, Jennings, & Palmer, in press). Such results correspond well with the broader typical performance literature.…”
Section: Modes Of Measurementsupporting
confidence: 72%
“…Multiple authors have suggested educational training as a way to improve EI (Berman and West, 2008;Gignac et al, 2012;Laabs, 1999;Oginska-Bulik, 2005;Ornstein and Nelson, 2006;Pilkington et al, 2012;Slaski and Cartwright, 2003;Zijlmans et al, 2011) and empirical data suggest that training can effectively increase EI (Gignac et al, 2012;Herpertz et al, 2016;Khodayarifard et al, 2012;Slaski and Cartwright, 2003;Zijlmans et al, 2011). One study found evidence to support increases in emotional identification and emotion management abilities among individuals who were trained in EI (Nelis et al, 2009).…”
Section: Emotional Intelligence Development and Nursingmentioning
confidence: 99%